The exploding worldwide cancer burden. Issue 1 (1st January 2004) - Wilson, C. M.; Tobin, S.; Young, R. C.
Abstract : Although age-adjusted cancer death rates have started to decline in the United States and other developed nations – thanks in large part to widespread screening programs that detect cancers at early, treatable stages – cancer in developing countries is on the rise. Ironically, rising life expectancy in those nations along with the adoption of 'Western' lifestyles will leave many more people vulnerable to cancer. Unfortunately, the early detection tools and treatment technology that have helped control cancer in wealthier lands are often not readily available in many other countries. Much of this increased cancer burden will take the form of cancers that affect women – not only breast, cervical, and other gynecologic cancers but colorectal cancer, lung cancer, and other malignancies related to tobacco. Physicians specializing in cancer care for women need to be alert to every opportunity to improve cancer screening and prevention among the growing, aging populations of less-developed countries. Less precise but less costly and more widely available screening techniques may save thousands more lives than the most sophisticated technology because low-cost programs can be applied widely instead of being reserved for a fortunate few. In addition, education and prevention efforts directed toward tobacco use need to be put in place to help stem an epidemic of tobacco-related cancers that has largely peaked in developed countries but looms ominously in the future of developing nations.